2022
DOI: 10.1002/jmv.27877
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir‐based therapy for late pregnant women and infants with severe chronic hepatitis C: A case series study

Abstract: Data on sofosbuvir-based therapy for pregnant women and infants with severe chronic hepatitis C (CHC) are lacking. Two late pregnant women and one female infant with severe CHC were enrolled for treatment. Pregnant Women 1 and 2 and Infant 3 were 30, 33, and 1.2 years old, respectively; the gestational ages of pregnant Women 1 and 2 were 31 and 26 weeks, respectively. Notably, pregnant Women 1 and 2 and Infant 3 had hepatitis C virus (HCV) RNA levels of 139 000, 198 000, and 8 450 000 IU/ml; alanine aminotrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Despite the fact that none of the aforementioned drugs are deemed safe for use during pregnancy and no clinical trials have been performed in this patient population group, we did find reports of their use during pregnancy. Velpatasvir, ledipasvir, paritaprevir, and sofosbuvir all have been previously used during pregnancy (AbdAllah et al 2021;Zeng et al 2022;Curtis and Chappell 2023;Kislovskiy et al 2021;Chappell et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that none of the aforementioned drugs are deemed safe for use during pregnancy and no clinical trials have been performed in this patient population group, we did find reports of their use during pregnancy. Velpatasvir, ledipasvir, paritaprevir, and sofosbuvir all have been previously used during pregnancy (AbdAllah et al 2021;Zeng et al 2022;Curtis and Chappell 2023;Kislovskiy et al 2021;Chappell et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…& ]. Successful DAA treatment has been described in several paediatric liver transplant candidates [55,56] and at least two adolescent kidney transplant recipients [57]. To our knowledge, there has not yet been published experience with intentional transplant of solid organs from HCV-viraemic donors to paediatric recipients.…”
Section: Key Pointsmentioning
confidence: 99%
“…Several additional case reports and small case series report intentional DAA treatment starting at the second or third trimester of pregnancy with 100% SVR12 in mothers completing therapy and no cases of vertical transmission [56,102,103]. Abdallah et al [104 & ] reported first trimester DAA exposure in 100 women who became pregnant while on DAA, with no obvious maternal or foetal safety signal observed.…”
Section: Direct-acting Antiviral Treatment For Prevention Of Paediatr...mentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of direct-acting antiviral agents (DAAs) with over 95% effectiveness in treating patients with chronic HCV infection 19 prompted the World Health Organization (WHO) to formulate the “Global Health Sector Strategy on viral hepatitis” with a goal of eliminating HCV infection by 2030. 20 , 21 While the use of DAAs for HCV in pregnancy lacks extensive clinical trial evidence, 22 , 23 , 24 , 25 , 26 recent recommendations from the American Association for the Study of Liver Diseases (AASLD) and the Infectious Diseases Society of America (IDSA) suggest that DAA treatment may be considered on a case-by-case basis, taking into account potential risks and benefits. 27 Moreover, despite recommendations advocating for universal and risk-based HCV screening among adults aged 18 to 79, 27 , 28 with a particular emphasis on pregnant women, the screening for HCV in women of childbearing ages and pregnant women remains uncommon.…”
Section: Introductionmentioning
confidence: 99%